“Trascurabili realtà”. Lavoro produttivo e riproduttivo nelle Ore migliori di Giovanni Giudici - Cappello, Massimiliano (Status Quaestionis, 2019)
This paper discusses Giovanni Giudici’s "Le ore migliori" from both a literary and a political perspective. The poetry, originally conceived for "L’educazione Cattolica" (1963), will later be included in his first major poetical book, "La vita in versi" (1965): in his attempt to communicate the ambiguous impact of the Italian economic miracle on the average man, Giudici not only reflects in strictly Marxist terms (like labour and alienation), but focuses also on women’s conditions, in order to underline a common situation of servitude which compare them to men. Distinguishing between a productive and a reproductive side of labour, Giudici proves himself not only an avid reader, but also a precursor of that feminist struggle for salary which will not be fully emerging in the Italian debate until 1968.